Geopark Owadów-Brzezinki - Błażejowski, Błażej; Czubla, Piotr (Acta Geographica Lodziensia, 2024)
Geological objects across Poland primarily benefit from protection through their inclusion within national and landscape parks, nature reserves and various environmental conservation measures. The most captivating geological sites in the country are catalogued within the Central Register of Geosites of Poland. Globally, the most significant means of promotion of geological heritage are through UNESCO Global Geoparks. As of March 2024, there are over 200 such geoparks worldwide, with only three situated in Poland. The precise definition of a geopark remains absent in Polish legislation and is therefore used quite freely. Among the designations made in this manner was the geological education centre at the "Owadów-Brzezinki" quarry near Opoczno. This centre owes its existence to the exemplary cooperation of local authorities, industry stakeholders and scientific community. It allows the dissemination of knowledge about a world-class palaeontological site, where dozens of new species of Late Jurassic fauna have been found and documented, including ammonites, horseshoe crabs, lobster-like crustaceans, ichthyosaurs, plesiosaurs and many others. The site’s exceptionally rich and perfectly preserved fossil marine fauna qualifies it as a Fossil Lagerstätte – a repository of extraordinary fossils. Researchers have reconstructed the environmental conditions conductive to the accumulation and survival of these unique specimens. Upon the completion of planned investments by local authorities, the "Owadów-Brzezinki" Geopark may become a potential nucleus for another Polish UNESCO Global Geopark. Undoubtedly, its establishment will further catalyse the growth of geotourism in the region.